1998
DOI: 10.1039/a802813c
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational modes and structures of lanthanide halide–alkali halide binary melts LnBr3–KBr (Ln=La, Nd, Gd) and NdCl3–ACl (A=Li, Na, K, Cs)

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 25 publications
9
56
0
Order By: Relevance
“…3). It is consistent with the results of Raman spectroscopy investigations of these systems [14], providing evidences for increasing stability of [NdCl 6 ] 3− complexes with the increase of alkali metal atomic number in solutions with molar fraction of NdCl 3 ≤ 0.25. In more concentrated solutions, changes of internal mobility of Nd 3+ are small, and this fact, according to some authors [5,6], suggests that electric charge in these melts is transferred primarily by Ln 3+ cations and chloride anions.…”
Section: Tablesupporting
confidence: 89%
See 1 more Smart Citation
“…3). It is consistent with the results of Raman spectroscopy investigations of these systems [14], providing evidences for increasing stability of [NdCl 6 ] 3− complexes with the increase of alkali metal atomic number in solutions with molar fraction of NdCl 3 ≤ 0.25. In more concentrated solutions, changes of internal mobility of Nd 3+ are small, and this fact, according to some authors [5,6], suggests that electric charge in these melts is transferred primarily by Ln 3+ cations and chloride anions.…”
Section: Tablesupporting
confidence: 89%
“…(5) and seem to suggest the increase of neodymium cations mobility at low concentrations of NdCl 3 . However, if the decrease of Nd 3+ mobility at medium concentrations of neodymium chloride is validated by formation of complexes in the melt [14], there are no arguments for the increase of the mobility at low concentrations. This range of concentrations should be investigated more carefully, especially for alkali metals with higher atomic number (cesium in the first place, but also rubidium and potassium), also due to negative values of Nd 3+ ions mobility in the CsCl-NdCl 3 system at y Nd < ≈0.6, suggesting 'hauling' effect of chloride ions on neodymium cations due to stronger interactions in negatively charged complex forms.…”
Section: Tablementioning
confidence: 90%
“…The model used for describing the properties of liquid phase in the investigated system has significant influence on the result of the CALPHAD calculation. The liquid phase of lanthanide(III) halide- alkali metal halide systems is an associated liquid [19]. Existence of the associates in a system always results in a deviation from the behavior of regular solutions.…”
Section: Calphad Methodsmentioning
confidence: 99%
“…Raman spectroscopic investigations [29] showed that octahedral LnBr 6 3− ions are formed in LnBr 3 -MBr liquid mixtures. These ions constitute the predominant species in the MBr-rich liquid mixtures.…”
Section: Electrical Conductivitymentioning
confidence: 99%